1977
DOI: 10.1111/j.1600-0447.1977.tb00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Homicidal aggession in schizophrenic men

Abstract: In a sample of 205 hospitalized schizophrenics, 59 men were found who made verbal threats to kill or physical attacks some time during their illness. All homicidal aggression occurred during active phases of psychosis, typically in a setting of acute excitement and in recurrent illnesses. Paranoid diagnoses were overrepresented. Closely related females were the prime targets, suggesting a resentment of dependence on a woman. An impersonal, compulsive urge appears to be the motivating force leading to physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

1978
1978
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 6 publications
1
26
0
3
Order By: Relevance
“…The non-planned, explosive violence observed with catatonic excitement or psychotic agitation is self-evidently far more impulsive than premeditated (Planansky & Johnston, 1977). Studies of aggressive behavior among schizophrenic subjects generally record whether the acts were related to delusions, hallucinations, or psychotic disorganization, but do not comment on whether the acts were also impulsive, compulsive, or premeditated.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The non-planned, explosive violence observed with catatonic excitement or psychotic agitation is self-evidently far more impulsive than premeditated (Planansky & Johnston, 1977). Studies of aggressive behavior among schizophrenic subjects generally record whether the acts were related to delusions, hallucinations, or psychotic disorganization, but do not comment on whether the acts were also impulsive, compulsive, or premeditated.…”
Section: Discussionmentioning
confidence: 98%
“…Disorders with prominent delusions, such as Schizophrenia, Paranoid Type (Planansky & Johnston, 1977;Tardiff & Sweillam, 1982) have a stronger association with violence than disorders that are not so marked by delusions. Taylor and colleagues (1994), however, point out that such studies do not always take into account the diagnostic distribution of the study population.…”
Section: Delusionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Others have suggested that aggression is not predicted by sex, psychiatric diagnosis or positive psychotic features, but by younger age, fewer years of illness and contemporaneous alcoholism and substance abuse (Kay et al, 1988). For some time command hallucinations were regarded as particularly significant (Planasky and Johnston, 1977;Yesavage 1983). Subsequently, it has been suggested that the presence of any psychotic symptom increases the risk, not just command hallucinations (Hellerstein et al, 1987).…”
Section: Introductionmentioning
confidence: 97%
“…Examination of schizophrenic patients who had committed violent crimes revealed that a very large majority of them had been psychotic at the time of the offence (Planansky & Johnston, 1977;Taylor, 1985). However, Virkkunen (1974) reported that only about one third of violent offences by schizophrenics are committed during a psychotic episode.…”
Section: Violent Behaviour In the Context Of Schizophrenic Symptomatomentioning
confidence: 99%